Enhancing EFL Students’ Writing Performance through Scaffolding: A Quasi-Experimental Study - Nugraha, Muhammad Setya; Mah’mudah, Faiqah (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to investigate the effect of the scaffolding teaching strategy on students’ writing achievement in recount text at Junior High School 30 Merangin. Writing is a complex skill that requires mastery of various components, including content, organization, vocabulary, grammar, and mechanics. However, many students still face difficulties in developing ideas and organizing their writing. To address this issue, scaffolding was implemented as a structured instructional strategy to support students throughout the writing process. Methodology: This research employed a quantitative approach using a quasi-experimental posttest-only control group design. The sample consisted of 64 eighth-grade students, divided into an experimental group and a control group, each comprising 32 students. The experimental group received instruction using the scaffolding strategy, while the control group was taught using the Scientific Approach. Data were collected through a writing post-test and analyzed using descriptive statistics and an independent sample t-test. Main Findings: The experimental group achieved a higher mean score (M = 83.10) compared to the control group (M = 75.20). The result of the t-test (t = 5.982) indicated a statistically significant difference between the two groups at the 0.05 significance level. This suggests that the scaffolding strategy had a positive effect on students’ writing achievement. Novelty/Originality of this study: Scaffolding is an effective teaching strategy that can enhance students’ writing performance, particularly in organizing ideas and developing coherent texts. This study contributes to EFL pedagogy by providing empirical evidence of the effectiveness of scaffolding in improving students’ writing skills.